Inter-trait relation studies for quantative production of marigold - Priyanka Kumari,; Deepti Singh,; Rakesh Kumari, (Annals of Agricultural Research, 2026)
Correlation studies were carried out among twenty important parameters of marigold for different yield attributing traits in order to differentiate the contribution made by each parameter towards total flower yield. The results revealed that the genotypic correlation were higher than the phenotypic correlation for the characters obtained, indicating the high heritable nature of the characters. Number of leaves per plant number of primary branches per plant, number of flowers per plant and average fresh weight of flower were reported highly significant and positive correlation with flower yield per plant, whereas stem diameter and 100 seed weight were found significant and positive correlated with flower yield per plant at both genotypic and phenotypic level. Since these association are in desirable direction, hence selection of these traits may ultimately improve the total flower yield.